Strategies for improving complementary feeding practices in informal settlements of Mumbai - Jayaraman, Anuja; Chanani, Sheila; Waingankar, Anagha; More, Neena Shah; Huestis, Arja; Banthia, Jayant; Pantvaidya, Shanti (International Food Policy Research Institute, 2015)
In 2014, a baseline survey sampled 2,582 children under the age of three from a population of 150,000 within the informal settlement of Dharavi, Mumbai, one of the largest slums in Asia. The survey found alarming levels of malnutrition among children—18 percent of the children under three were wasted, 25 percent were stunted, and 28 percent were underweight (Aahar 2014).